Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Solvent-free carbonylation of glycerol with urea using metal loaded MCM-41 catalysts - Kondawar, S. E.; Potdar, A. S.; Rode, C. V. (RSC Advances, 2015)
Reacting glycerol with urea is the most attractive option for the production of glycerol carbonate (GC) as it utilizes two inexpensive chemicals readily available in the chemical cycle. The overall result is the chemical fixation of carbon dioxide. A Zn/MCM-41(im) catalyst prepared by a wet impregnation method exhibited excellent activity for the reaction of glycerol and urea with 75% glycerol conversion and 98% selectivity to GC. Such excellent activity of the catalyst is explained based on the presence of both basic and acidic sites on the same catalyst which activates the glycerol and urea molecules, respectively.

Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts - Kondawar, S. E.; Mane, R. B.; Vasishta, A.; More, S. B.; Dhengale, S. D.; Rode, C. V. (Applied Petrochemical Research, 2017)
Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but glycerol conversion achieved was twice with Zn/MCM-41 as a catalyst. Further to that increase in Zn loading from 2 to 5% resulted in increase in glycerol conversion from 63 to 82%. The prepared catalysts were characterized by XRD, NH3 and CO2-TPD and effects of reaction parameters such as catalyst loading, glycerol to urea mole ratio and temperature on glycerol conversion and GC selectivity in batch mode of operation were also studied. Time on stream activity of 5% Zn/MCM-41 catalyst for continuous carbonylation of glycerol was also studied for ~100 h with an average conversion of ~55% and complete selectivity to GC. This indicated five times lower productivity of GC per h due to lower residence time than that in a batch operation as compared to that of a continuous operation. Activation energy estimated from the Arrhenius plot was found to be 39.82 kJ mol−1 suggesting that the reaction is kinetically controlled. A reaction pathway mediated by acid and basic sites of the Zn/MCM-41 catalyst is also proposed.
Keywords: Acid–base ratio; Continuous process; Glycerol carbonate; Glycerol-urea carbonylation; reaction pathway; Supported Zn; Zn loading

Tandem synthesis of glycidol via transesterification of glycerol with DMC over Ba-mixed metal oxide catalysts - Kondawar, S. E.; Patil, C. R.; Rode, C. V. (ACS Sustainable Chemistry & Engineering, 2017)
Glycerol carbonate (GC) and glycidol (GD) are commercial products possible from glycerol transformation, which has become a subject of great importance. Among several basic catalysts screened in this work, BaO showed the highest glycerol conversion of 71% with almost complete selectivity to GC. A tandem synthesis of GD with a selectivity as high as 80% with 98% glycerol conversion could be achieved with mixed oxides of Ba and lanthanides (La and Ce) prepared by the coprecipitation method. Although BaO alone showed the highest basicity as measured by CO2 TPD, tuning of basicity by incorporation of CeO2 resulted in the formation of GD. Incorporation of Ba into the ceria matrix induced oxygen vacancies in the cerium oxide material. The presence of u"/v" doublets at 888.7 and 903.2 eV, respectively, in XPS of the Ba-Ce sample also confirmed the oxygen vacancies in the lattice. In this tandem approach to GD, the subsequent decarboxylation of initially formed GC was due to the presence of a CeO2 lattice with defects, which is known to be the best for CO2 adsorption. Increase in both catalyst loading and temperature showed a dramatic enhancement in GD selectivity. A plausible reaction pathway for the transesterification of glycerol with DMC to give GC followed by its decarboxylation to GD is also proposed based on the structural characterization and activity studies.